Disease and economic burden of prostate cancer in Malaysia: a review - Norzaher Ismail,; Aniza Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction In Malaysia prostate cancer is ranked as fifth type of cancer among male. Unlike other cancers, prostate cancer is slow growth type of cancer; hence most patients may be asymptomatic despite having the disease. The burden associated with prostate cancer disease started from the diagnosis, the progress of disease and the varying impact of the available treatment options till the quality of life. The review focused on the disease and economic burden of prostate cancer disease towards country and patient personally. Methods A search was conducted to review related published studies on economic burden of the prostate cancer through PubMed/MEDLINE, Google Schorlar and Science Direct searching engines databases using keywords: Prostate cancer, economic burden and disease burden, treatment burden and treatment cost. For exploration on the burden itself, the keywords used were economic cost, mortality, morbidity, quality of life, treatment burden, palliative care. A review on the morbidity and mortality comparing global, Asian and Malaysia situation reviewed from previous review paper and online data. Conclusions Economic burden of prostate cancer include quality of life, treatment cost and palliative cost and palliative support care system. Development and improvise of the treatment facilities and equipment, strong knowledge and clinical training of staff in the treatment of cancer should be well planned in order to reduce the increasing burden of prostate cancer in Malaysia.